Vascular Accesses - Fukuda Borges Moreira, Gutemberg; de Oliveira Leite, Tulio Fabiano; Bertanha, Matheus [UNESP]; Abreu, Phillipe; Malgor, Rafael (Springer Nature, 2025)
The first reports on the use of vascular accesses described date back to the eighteenth century, when Stephen Hales promoted vascular catheterization to measure venous and arterial pressures in animals. In the following century, Faivre [5] performed the first blood pressure measurement in humans. The continuous improvement of equipment for intravascular access has enabled the improvement of care to the patient in a severe condition.